1992
DOI: 10.1136/hrt.68.7.16
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular filling characteristics in pulmonary hypertension: a new mode of ventricular interaction

Abstract: Objective-To examine the effects of pulmonary hypertension on left ventricular diastolic function and to relate the findings to possible mechanisms of interdependence between the right and left sides of the heart in ventricular disease.Design-A retrospective and prospective analysis of echocardiographic and Doppler studies.Setting-A tertiary referral centre for both cardiac and pulmonary disease.Patients-29 patients with pulmonary hypertension (12 primary pulmonary hypertension, 10 pulmonary fibrosis, five atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
69
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 16 publications
(9 reference statements)
5
69
0
2
Order By: Relevance
“…Several authors have previously noted the high prevalence of LV diastolic dysfunction in patients with PAH. [1][2][3]14 However, most of these studies included patients with chronic thromboembolic disease or a heterogenous group of patients with PAH. In our cohort, which consisted of carefully selected patients with hemodynamic criteria for PAH, 9 we observed that nine out of 10 patients had impaired LV relaxation (grade I diastolic dysfunction) by echocardiographic criteria, with redistribution of the LV fi lling from early to late diastole.…”
Section: Relationship Of LV Diastolic Function With Hemodynamics Paramentioning
confidence: 99%
See 3 more Smart Citations
“…Several authors have previously noted the high prevalence of LV diastolic dysfunction in patients with PAH. [1][2][3]14 However, most of these studies included patients with chronic thromboembolic disease or a heterogenous group of patients with PAH. In our cohort, which consisted of carefully selected patients with hemodynamic criteria for PAH, 9 we observed that nine out of 10 patients had impaired LV relaxation (grade I diastolic dysfunction) by echocardiographic criteria, with redistribution of the LV fi lling from early to late diastole.…”
Section: Relationship Of LV Diastolic Function With Hemodynamics Paramentioning
confidence: 99%
“…pressure gradient, 15,16 leading to decrease in LV compliance. 1,2,14,[17][18][19] Other causes include an increase in RV tension that leads to prolonged RV myocardial shortening with abnormal relaxation of the interventricular septum that impairs RV systole and LV diastole, 1,20 decrease in LV torsion, 21 delay in early diastolic LV untwisting, 22 reduction in the preload, 4,5,21 diastolic asynchrony in the anterior-lateral or apical regions, 23,24 and intrinsic disease of the left ventricle. [25][26][27] In our study, as well as others, 2,14 septal displacement (measured as eccentricity index) was predominantly observed in systole and early diastole, possible decreasing LV compliance and explaining impaired LV relaxation.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Impaired diastolic function may precede systolic ventricular dysfunction (13,14), and it influences the performance of the contralateral ventricle via ventricular interdependence (23,34,39). The gold standard for determination of right ventricular (RV) [and left ventricular (LV)] diastolic function is still considered to be cardiac catheterization with simultaneous high-fidelity pressure and volume measurements (32).…”
mentioning
confidence: 99%